Flavour science proceedings from XIII Weurman Flavour Research Symposium - Ferreira, Vicente; Lopez, Ricardo (Elsevier Science, 2013)
Flavor science is continually evolving. Remaining current with the latest research and establishing a broad and sound understanding of the major developments and breakthroughs can be a challenge. The Weurman Flavour Research Symposium has long been regarded as the premier professional meeting focused on the science of flavor. Flavour Science, an extensive review of the most recent symposium, presents the latest in flavor research, enriching the chemistry-based vision of most flavorists and flavor chemists with understanding from a broad range of fields, including human physiol.
11.2.2 Electric Cell Substrate Impedance Sensing (ECIS).
Includes index.
Keywords: senzorická analýza; potraviny; potravinářská chemie; čich; chuť; chemosenzory; biotechnologie; sensoric analysis; food; food chemistry; smell; taste; chemosensors; biotechnology; sborníky konferencí; elektronické knihy; proceedings of conferences; electronic books